Anesthetic considerations in the Grand Patient Burned - Rubilar Moya, Manuel; Arancibia Ibacache, Hernán (Boletín de Anestesia, 2022)
Burns is a life-threatening challenge for health services and especially for the anesthesiologist. During the evolution of this disease, the patient will undergo hemodynamic and metabolic changes that will influence our management and the decisions of the anesthetic plan. Adequate fluid management is essential in the first hours of resuscitation, and underdosing or overdosing has significant risks in terms of morbidity and mortality in these patients. The evaluation and management of the airway will require special attention since the anatomical distortions and the risk of inhalation injury will lead to obstruction, distress, and respiratory insufficiency of rapid installation if not appropriately treated. The painful stimulus they experience will have a high risk of developing chronicity.Multimodal therapies will be crucial for their adequate treatment. In this review, we explore considerations from the anesthetic point of view of the severely burned patient.